The Off-Label Use of Oxcarbazepine In Indonesia - Bangunawati Rahajeng; Zullies Ikawati; Tri Murti Andayani; Iwan Dwiprahasto (Acta Pharmaceutica Indonesia, 2018)
Oxcarbazepine is a second-generation anticonvulsant drug that is a keto analog of carbamazepine. Oxcarbazepine was approved by The National Agency of Drug and Food Control Indonesia (NA-DFC) for generalized epilepsy, tonic-clonic primary and partial epilepsy with or without secondary generalization. However, as other anticonvulsants, oxcarbazepine is also often used without approved indication (off-label). The aim of this study is to investigate the off-label use of oxcarbazepine through an observational study with retrospective data collection. Data were obtained from four hospitals in Yogyakarta, namely Dr. Sardjito Hospital, UGM Hospital, PKU Muhammadiyah Hospital and Bethesda Hospital. Off-label use of oxcarbazepine was identified based on official registration by NA-DFC Indonesia. The results of this study showed that the use of oxcarbazepine in 2014 was 224 prescriptions, which 117 (52.68%) was off-label. Most off-label indications according to ICD-10 were cephalgia 48 (41.03%), followed by trigeminal neuralgia 35 (29.91%), stroke 6 (5.13%) and others 29 (23.93%). From these study, the off-label use of oxcarbazepine was mostly in the cases of neuropathic pain.